Function of Cdc2p-dependent Bub1p phosphorylation and Bub1p kinase activity in the mitotic and meiotic spindle checkpoint - Yamaguchi, Satoko (Oxford University Press, 2003)
Cdc2p is a cyclin-dependent kinase (CDK) essential for both mitotic and meiotic cell cycle progression in fission yeast. We have found that the spindle checkpoint kinase Bub1p becomes phosphorylated by Cdc2p during spindle damage in mitotic cells. Cdc2p directly phosphorylates Bub1p in vitro at the CDK consensus sites. A Bub1p mutant that cannot be phosphorylated by Cdc2p is checkpoint defective, indicating that Cdc2p-dependent Bub1p phosphorylation is required to activate the checkpoint after spindle damage. The kinase activity of Bub1p is required, but is not sufficient, for complete spindle checkpoint function. The role of Bub1p in maintaining centromeric localization of Rec8p during meiosis I is entirely dependent upon its kinase activity, suggesting that Bub1p kinase activity is essential for establishing proper kinetochore function. Finally, we show that there is a Bub1p-dependent meiotic checkpoint, which is activated in recombination mutants.